Corporate Governance and Financial Performance of Deposit Money Banks in Nigeria: Array - Ogunmakin, Adeduro Adesola; Fajuyagbe, Samson Bamikole; Alayo, Richard Adetunji (EuroEconomica, 2020)
The study examined effects of corporate governance on financial performance of selected deposit money banks in Nigeria. The study used 10 deposit money banks randomly selected from 21deposit money banks listed on the Nigeria stock market. The study sourced for data via the annual reports of the chosen banks over a period of 10 years spanning from 2009 to 2018. Data collected were analyzed using both descriptive and inferential methods of study. Descriptive analysis conducted within the study included mean analysis, measure of dispersion, minimum and maximum analysis, followed by correlation analysis, pooled OLS estimation, fixed effect estimation, random effect estimation, and post estimation test like restricted F-test, Hausman test, Pesaran cross sectional independence. The study revealed that board size exerts a negative and significant effect on the performance of Deposit Money Banks in Nigeria -0.8462(p=0.0090.05). It had been also, revealed that gender diversity exerts a positive but insignificant effect on the financial performance of Deposit Money Banks in Nigeria to the tune of 5.1647(p=0.685>0.05). The study concluded that corporate governance exerts a big effect on the financial performance of Deposit Money Banks in Nigeria. The study recommended that the monitoring function of the members of the board of Deposit Money Banks should be directed at pressing must be productive and convey about a rise within the profit level and therefore the management of those banks should know that tons of advantages are implanted in corporate governance if accorded the proper place within the management of the affairs.